SecGRID: model for maintaining trust in large-scale dynamic environments. (18th December 2008) - Spanek, Roman
The paper describes a new model for treating trust in reconfigurable groups of users with special accent on maintaining trust in the next generations of applications. The proposed model uses properties of weighted hypergraphs for description of possibly complicated trust relationships between and within groups of users. The model flexibility enables description of the relations such that these relations are preserved under frequent changes in their structure or trust. The presented ideas can be for their generality straightforwardly generalised to other concepts describable by weighted hypergraphs. The consistency of the proposal was verified in a couple of experiments with our pilot implementation SecGRID.